The analgesic efficacy of erector spinae plane block versus paravertebral block in thoracic surgeries: a meta-analysis - Fenta, Efrem; Kibret, Simegnew; Hunie, Metages; Tamire, Tadese; Mekete, Getachew; Tiruneh, Abebe; Fentie, Yewlsew; Dessalegn, Kaletsidik; Teshome, Diriba (Frontiers in Medicine, 2023)
Background Acute postoperative pain after thoracic surgery might lead to chronic postsurgical pain (PSP), which lowers quality of life. The literature suggests thoracic paravertebral block (PVB) as a pain management approach. The ESPB (erector spinae plane block) is regarded to be an effective PVB alternative. The analgesic efficacy of the two analgesic therapies is controversial. The purpose of this study is to compare the analgesic efficacy of ESPB and PVB in preventing acute PSP. Methods We searched relevant articles in PubMed, Cochrane Library, Embase, Web of Science, and Google Scholar databases. The primary outcome was postoperative pain score, with secondary outcomes including analgesic consumption, the frequency of rescue analgesia, and postoperative nausea and vomiting. Results This meta-analysis included ten RCTs with a total of 670 patients. PVB significantly lowered the pain scores at movement at 12 h following surgery as compared to the ESPB. The PVB group used much less opioids within 24 h after surgery compared to the ESPB group. However, there were no significant differences between the groups in terms of postoperative rescue analgesia or in the incidence of postoperative nausea and vomiting (p > 0.05). Conclusion PVB produced superior analgesia than ESPB in patients who underwent thoracic surgeries. In addition, PVB demonstrated greater opioid sparing effect by consuming much less opioids. Systematic review registration This trial is registered on PROSPERO, number CRD42023412159.